New legal regulations on current medical problems - Iwona Wrześniewska-Wal; Dariusz Hajdukiewicz; Anna Augustynowicz; Lidia Janiszewska; Emilia Sarnacka; Michał Waszkiewicz (Wiedza Medyczna, 2022)
The article consists of three parts showing the changes that took place in the health care law in 2021. The main goal was to discuss those legislative changes that, according to the authors, are innovative and in the future will have a significant impact on the shape of the entire health care system in Poland.